Overview of key performance indicators (MCIT: Proceedings of International scientific and practical conference, 2019)
A set of key performance indicators (KPIs) formanufacturing operation management is introduced in the ISO22400 standart. In this paper, a framework is introduced in orderto solve the problem of dividing into types all the 38 KPIs.
Keywords: key performance indicators; KPI; KPIs; ISO 22400